Cross-cultural adaptation and psychometric evaluation of the Chinese version of Childbirth Experience Questionnaire 2.0 - Wu, Jiahui; Hong, Yan; Guan, Huici; Huang, Mulan; Liang, Jieqiong; Wen, Zhimin; Gao, Yulin; Feng, Xiangang (Frontiers in Psychiatry, 2025)
BackgroundChildbirth experience is a key determinant of maternal psychological well-being, and WHO emphasize promoting positive birth experiences. The Childbirth Experience Questionnaire (CEQ) is a widely used measure of women’s perceptions of labor and delivery. An improved version of this instrument, the CEQ 2.0, has not yet been adapted or psychometrically validated for use in mainland China. This study aimed to validate a Mainland version of CEQ 2.0 (CEQ 2.0-M) among Chinese postpartum women.MethodsA three-stage cross-sectional psychometric study was conducted among 700 postpartum women recruited from a tertiary hospital in mainland China (350 for EFA, 350 for CFA). Item analysis and dimensional refinement were applied to revise the original 25-item Chinese CEQ 2.0 before factor analyses. Structural validity was evaluated using parallel analysis, exploratory factor analysis (EFA), and confirmatory factor analysis (CFA). Reliability was assessed via Cronbach’s α and McDonald’s ω, and validity evidence included convergent, discriminant, concurrent, and known-group analyses.ResultsIn Stage 1, item analysis and theoretical review led to the refinement of the original Chinese CEQ 2.0, resulting in a four-factor version with improved conceptual clarity. In Stage 2, exploratory factor analysis supported this four-factor structure, explaining 53.2% of the total variance. Confirmatory factor analysis in Stage 3 indicated acceptable model fit (χ2/df = 2.590; AGFI = 0.892; GFI = 0.927; CFI = 0.949; TLI = 0.934 and RMSEA = 0.068). Internal consistency was satisfactory, with Cronbach’s α = 0.65–0.91 and McDonald’s ω = 0.65–0.91 across subscales, and 0.84 and 0.80 respectively for the total scale. Evidence of convergent, discriminant, concurrent, and known-group validity further supported the scale’s psychometric robustness.ConclusionsThe CEQ 2.0-M shows satisfactory psychometric properties and offers a valid, reliable instrument for assessing childbirth experiences among Chinese postpartum women. Its concise structure and established construct validity support its use in both clinical practice and research, particularly in developing countries seeking culturally appropriate tools for perinatal care evaluation.